Jambi City community transportation modes and influencing factors - Junaidi Junaidi; Yulmardi Yulmardi; Hardiani Hardiani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
This study aims to analyze the Jambi City community transportation modes' needs and diversity and influencing factors. This study uses primary data and secondary data. Primary data comes from a sample of households in Jambi City. Meanwhile, secondary data comes from related agencies or institutions at the National, Provincial, and City of Jambi levels related to transportation macro conditions. This study uses descriptive statistical analysis to analyze the diversity of transportation modes used in Jambi City. Meanwhile, to analyze the factors that influence transportation mode choice, it is estimated using logit ordinal regression models. The analysis results found that the primary mode of transportation used by the Jambi City community was personal motorbikes. Public transportation is the second choice, and the use of private cars is the third option. The choice of transportation mode is influenced by gender, main activity, car ownership, motorcycle ownership, and household income.